2017
DOI: 10.1037/aap0000081
|View full text |Cite
|
Sign up to set email alerts
|

Does emotion regulation moderate the discrimination-adjustment link for adopted Korean American adolescents?

Abstract: Growing up in a White family does not necessarily protect internationally adopted Korean Americans raised in White families from the pernicious effects of discrimination. Emotion regulation strategies may buffer the effects of discrimination on psychological adjustment, yet little research has been conducted on these links. To fill this gap, we examined the relationship between emotion regulation, discrimination and psychological adjustment in a sample of adopted Korean American adolescents (N ϭ 115). Using bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although issues of race have not been largely represented in the discourse concerning transnational adoption, existing research suggests that ATAs are not exempt from racial stress and prejudice (Kim et al, 2010; Lee et al, 2015; Qin et al, 2017). As they age and develop more cognitive maturity, studies suggest that ATAs often face a variety of racial stressors.…”
Section: Ata Racial–ethnic Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although issues of race have not been largely represented in the discourse concerning transnational adoption, existing research suggests that ATAs are not exempt from racial stress and prejudice (Kim et al, 2010; Lee et al, 2015; Qin et al, 2017). As they age and develop more cognitive maturity, studies suggest that ATAs often face a variety of racial stressors.…”
Section: Ata Racial–ethnic Experiencesmentioning
confidence: 99%
“…Although it is not uncommon for parents and children to hold different perspectives, studies suggest there is a greater likelihood for relational conflict (Kim, Zarit, Birditt, & Fingerman, 2014) and adjustment difficulties (Ohannessian, 2012) when family members hold significantly different views about sensitive issues, such as racism. In addition, it is particularly important to explore parents’ ability to recognize the racial nature of ATAs’ experiences, given that racial prejudice can have a negative impact on youth of color (García Coll et al, 1996; Qin, Kim, Su, Hu, & Lee, 2017) and has been specifically linked with increased behavioral difficulties (Hjern, Lindblad, & Vinnerljung, 2002; Lee, 2010) and higher psychological distress among international adoptees (Lee, Lee, Hu, & Kim, 2015). Overall, the study results are intended to provide a more critical understanding of the experiences of ATAs and other transnational adoptees as people of color.…”
mentioning
confidence: 99%
“…Another critical factor to consider is exposure to discrimination and oppression. For example, racial discrimination was associated with greater ER difficulties and psychopathology among Black, Latino, and multiracial gay and bisexual men (English, Rendina, & Parsons, 2018), and greater psychopathology among adopted Korean American adolescents (Qin, Kim, Su, Hu, & Lee, 2017), and Asian participants (Hwang & Goto, 2008). In the current study, race served as a poor proxy for cultural values or experiences of discrimination, and it is impossible to determine whether the differences that emerged are specifically due to cultural background, experiences of discrimination, or other sociocultural/sociopolitical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic identity and discrimination. Six studies explored the relationship between psychological adjustment, ethnic identity development and experiences of discrimination, mostly among internationally adopted children (Juffer and van IJzendoorn;Lee, 2010;Qin, et al, 2017;Schires, et al, 2020;. Three US studies found that discrimination was linked to greater internalising and externalising problems, depressive symptoms and psychological distress (Lee; Schires; Qin) with another showing that discrimination was greater for parents of Asian and Latin American children than for white Eastern European children.…”
Section: Contextual Factorsmentioning
confidence: 99%